Self-interest versus collective action: understanding cross-class environmental perception, knowledge and behavior in Brazil - RAMALHO-GUEDES, Gilvan; LUIZ DO CARMO, Roberto (Papeles de Población; Vol. 19 Núm. 78 (2013), 2013)
This paper aims to seek evidence of environmentalism among the poor by asking two questions: i) is environmental perception, knowledge and behavior positively influenced by the socioeconomic status and objective environmental conditions of individuals?; ii) Does the nature of behavior (collective versus private) influence pro-environmental actions among the poor? Using novel household-level data representative of two metropolitan regions in the State of São Paulo, Brazil, we measure and describe perceptions and behavior about several environmental issues using the Grade of Membership (GoM) technique and fixed-effect logistic regression. Based on our findings, we argue that past evidence on low levels of pro-environmental behavior in low-income settings may reflect the inability of differentiating private (individual) from public (collective) environmental behavior. We address these limitations by including questions about actual and intended environmental behavior that explicitly differentiates individual from collective actions. This difference is key to understanding how low-income individuals overcome budget constraints, reducing the unitary cost of action.